A Mauritian Case Study of IT Governance and Green IT - Hardin-Ramanan, Sarita (2020)
From its small size to its resource constraints and vulnerability to climate instabilities, the Small Island Developing State of Mauritius faces multiple obstacles in its journey from an upper middle-income to a high-income economy. As highlighted in its 2030 Vision, the key to overcoming these issues lies in a digital and environmentally sustainable Mauritius. Organisational Information Technology (IT) needs to progress from its traditionally reactive function to a more pro-active, strategically aligned position. The effective governance of IT and Green IT is thus essential to maximise IT value in boosting productivity and sustainable practices within both the public and private sector. This chapter discusses the Mauritian legal and strategic environment through an IT governance and Green IT prism. With IT ranking high on the Mauritian government agenda, several laws and strategic plans were found to drive robust IT solutions for ecological and effective processes. However, many do not explicitly highlight the vital role of IT Governance and Green IT in effective IT use. The Mauritian legal framework, National Code of Corporate Governance, as well as national policies and plans therefore warrant improvement to further encourage the adoption of IT governance and Green IT measures for a green, digital Mauritius.